Exploring the role of individual level and firm level dynamic capabilities in SMEs’ internationalization - Mudalige, Darshana; Ismail, Noor Azizi; Abdul Malek, Marlin Marissa (Springer US, 2019)
This paper presents a multi-level model that examines the impact of dynamic capabilities on the internationalization of SMEs while taking into account the interactions among them. The purpose of the research is to understand the applicability of dynamic capabilities at the individual and the firm level to the SME internationalization process in developing country context and to assess to what extent a firm’s asset position and individual level dynamic capabilities influence the generation of firm level dynamic capabilities in SMEs. First, the dynamic capabilities theory was theoretically linked to the internationalization phenomenon. The relationships among firm-level dynamic capabilities, individual-level dynamic capabilities (owner specific dynamic capabilities), and internationalization were identified. The research framework and hypotheses were developed and empirically tested with 197 SMEs. The findings established that owner-specific dynamic capabilities have a positive influence on both firm dynamic capabilities and internationalization, and firm dynamic capabilities positively influence internationalization. It was also found that the market assets position measured as perceptual environmental dynamism positively influenced firm dynamic capabilities but structural and reputational asset positions of SMEs did not influence generation of firm dynamic capabilities. Moreover, firm dynamic capabilities had a mediation effect in the relationship between owner-specific dynamic capabilities and internationalization. Theoretically, this confirms the relevance of dynamic capability theory to internationalization and the possibility of integrating existing internationalization theories. Entrepreneurs, SME managers, and policy-makers could gain valuable insights on how entrepreneur and firm capabilities lead to better international prospects from this outcome.